Maternal Haploids Are Preferentially Induced by CENH3-tailswap Transgenic Complementation in Maize - Kelliher, Timothy; Starr, Dakota; Wang, Wenling; McCuiston, Jamie; Zhong, Heng; Nuccio, Michael L.; Martin, Barry (Frontiers in Plant Science, 2016)
Doubled haploid plants are invaluable breeding tools but many crop species are recalcitrant to available haploid induction techniques. To test if haploid inducer lines can be engineered into crops, CENH3 -/- and CENH3:RNAi lines were complemented by AcGREEN-tailswap-CENH3 or AcGREEN-CENH3 transgenes. Haploid induction rates were determined following testcrosses to wild-type plants after independently controlling for inducer parent sex and transgene zygosity. CENH3 fusion proteins were localized to centromeres and did not cause vegetative defects or male sterility. CENH3:RNAi lines did not demonstrate consistent knockdown and rarely produced haploids. In contrast, many of the complemented CENH3 -/- lines produced haploids at low frequencies. The rate of gynogenic haploid induction reached a maximum of 3.6% in several hemizygous individuals when backcrossed as males. These results demonstrate that CENH3-tailswap transgenes can be used to engineer in vivo haploid induction systems into maize plants.